Effect of Different Luting Methods on the Microtensile Bond Strength of CAD/CAM Resin Blocks - Alexandra Vinagre; Carla Delgado; Gabriela Almeida; Ana Messias; João Carlos Ramos (Biomimetics)
The widespread implementation of new CAD/CAM materials has led to the necessity of establishing an adequate luting protocol. The aim of this study was to evaluate the microtensile bond strength (μTBS) and the film thickness of different luting methods on CAD/CAM resin blocks. Five Brilliant Crios CAD/CAM blocks (Coltene/Whaledent) were sequentially sectioned into two halves, air abraded with 50 µm aluminum oxide, and luted according to five different cementation protocols: Brilliant EverGlow (BEG), Brilliant EverGlow with ultrasound application (BEG-US), preheated Brilliant EverGlow (BEG-H), Brilliant EverGlow Flow (BEGF), and Duo Cem® Trans (DC). Subsequently, the blocks were sectioned to obtain rods, which were then submitted to a microtensile bond strength test (n = 20). The surfaces were examined with optical microscopy to determine the failure mode and the bonding interface was assessed with scanning electron microscope (SEM) analysis. Bond strength values were analyzed using one-way ANOVA and Tukey’s post hoc tests (α = 0.05). The bond strength values varied with the different cementation protocols (p < 0.001): BEG (45.48 ± 18.14 MPa), BEG-US (42.15 ± 14.90 MPa), BEG-H (41.23 ± 15.15 MPa), BEGF (58.38 ± 15.65 MPa), and DC (81.07 ± 8.75 MPa). Regarding bond strength, DC presented significantly higher values than all other experimental groups (p < 0.050), whereas all luting methods using BEG presented similar values (p = 0.894). Adhesive failures were the predominant type. On SEM evaluation, all the luting materials presented a tight and homogeneous cement–block interface with variable film thicknesses. In conclusion, among the cementation protocols, the resin cement (DC) rendered the highest bond strength values. SEM analysis revealed that the lowest film thickness was associated with the flowable composite (BEGF).